Asian appearing women speaking into a microphone - Unknown:::Creator::::::::::::
Photograph shows a woman, who appears to be Asian American, holding a microphone and speaking. There are fabric banners on the wall and another banner on the table behind her. The banner on the table has Chinese characters on it.